EVALUATION OF THE SMALL FARMERS FUND IN THE AGRICULTURAL INITIATIVE IN IRAQ THROUGH THE COLLECTION EFFICIENCY OF LOANS FOR THE PERIOD 2009 – 2018 - Sanaa J. Mohammed; M. H. O. Al Khazeli; B. H. Al-Badri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
To evaluate and analyze the small farmers fund, one of the funds financed by the allocation of the Supreme Committee for the Agricultural Initiative, this fund finance the unconditioned plastic houses, beekeeping, field crops, winter and summer vegetable crops, protected tomato houses, olive trees services, planting of green silage by fixed sprinkler irrigation and to construct consulting offices. As the total number of loans granted to this fund reached nearly 481 billion dinars in all governorates, amounting to 38991 beneficiaries, constituting about 23% of the total loans disbursed during the study period, Baghdad governorate has 68.6 billion of total amounts of that fund and that consist 16.6% of it, then Anbar came in the second rank by 14.7% then Wasit came in the third rank by 12%, while Kirkuk came in the last. The study reached an analysis of the achievement ratios of the small farmers fund for the period 2009-2018 for all governorates, the provinces of Baghdad and Basra were highest share of this fund for the year 2009, while the lowest share for these year were for Mysan and Kirkuk. In 2010, Anbar has the highest share while Kirkuk was the lowest. In 2011-2012, the governorate of Baghdad ranked first, and the lowest were for Kirkuk governorate, in 2013, Anbar came to the first, the lowest was Kirkuk governorate, then Wasit governorate returned to first place with collection rates for 2014 and in 2015 Najaf was the first and for 2016 and 2017, the governorate of Baghdad came first. There is a clear decrease in the rates of late loan repayment in this fund because these loans are closely related to the guarantees that document the loans. Most of the guarantees of these loans are the bill only, whereby the amount of withdrawals loans of all kinds is proportional to the amount of the guarantee on the bill of exchange 40 million dinars. The study recommended the necessity of conducting a field survey of all the purposes that the small farmers fund.